Summary of Kansas State University swine enterprise record - Langemeier, Michael R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The Kansas Swine Enterprise Record Program evaluates biological and economic performance and is part of a cooperative record- keeping project with Extension personnel and swine producers in Kansas. Nebraska, and South Dakota. From January 1 to December 31, 1996, profit per cwt of pork produced by these producers (13 semiannual and 18 annual data) averaged $10.62 for the last 6 months of 1996 and $8.08 for the entire year. Producers in the top one-third in terms of profitability had average profits of $15.11 per cwt, whereas producers in the bottom one-third had average profits of $.73 per cwt for the year. Critical factors separating low- and high-profit producers included feed costs, unpaid labor, fixed costs, and death loss.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Swine; Enterprise; Records; Analysis; Profitability